The Roles of socio-environmental factors influencing the transmission, prevention, and control of COVID-19 and Tuberculosis disease: a review - Rahayu Othman,; Nazarudin Safian,; Mohd Rohaizat Hassan, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Over the past two years, coronavirus disease 2019 (COVID-19) and tuberculosis (TB) have killed over 5.7 million people globally. TB and COVID-19 continue to be significant public health problems worldwide. A growing body of research supports a link between socio-environmental factors and the transmission of COVID-19 and TB disease. This review article discussed the socio-environmental factors influencing the transmission, prevention, and control of COVID-19 and Tuberculosis disease. In this review, we highlight similarities and differences between these two infectious diseases and explore the roles of socio-environmental factors (air pollution exposure and climate change) and socioeconomic factors in disease transmission. A comprehensive, integrated TB-COVID-19 management for prevention and disease control, which includes administrative, engineering, environmental control, effective personal protective equipment, and community-based public health activities were discussed. Understanding the similarities and differences between these two infectious diseases and the role of socio-environmental factors in disease transmission helps in planning and strengthening an integrated system for disease prevention and control strategies.